2016
DOI: 10.1038/srep33201
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of sirtuin 3 in a murine model of sepsis-induced acute kidney injury

Abstract: Acute kidney injury (AKI) is a rapid loss of kidney function characterized by damage to renal tubular cells driven by mitochondrial dysregulation and oxidative stress. Here, we used a murine caecal ligation and puncture (CLP) model of sepsis-induced AKI to study the role of sirtuin 3 (SIRT3), a NAD+ dependent deacetylase critical for the maintenance of mitochondrial viability, in AKI-related renal tubular cell damage and explored the underlying mechanisms. CLP induced alterations in kidney function and morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
66
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 36 publications
10
66
1
Order By: Relevance
“…7A, F). This is consistent with a previous study showing that NAC inhibited the expression of NLRP3 protein (53).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…7A, F). This is consistent with a previous study showing that NAC inhibited the expression of NLRP3 protein (53).…”
Section: Discussionsupporting
confidence: 94%
“…ROS are well known activators of NLRP3 inflammasome. It is reported that NAC can block the transcription of NLRP3 and pro-IL-1b by scavenging of cellular ROS (53). Other research also found that mtROS scavengers can significantly inhibit the activation of NLRP3 inflammasome (53).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Various studies have demonstrated that excessive ROS promotes necroptosis in various cell types, whereas inhibiting ROS production reduces necroptosis (13)(14)(15)(16). In addition, previous studies revealed that ROS production is augmented in AKI, and that ROS lead to renal tubular epithelium injury via inflammasome activation, mitochondrion damage and tubular epithelium apoptosis (22)(23)(24)(25). To the best of our knowledge, there are no studies that have investigated the effect of ROS on necroptosis in renal tubular epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, overexpression of SIRT3 in THP-1 cells inhibited the activation of the NLRP3 inflammasome, whereas its knockdown stimulated its activation [91]. Not surprisingly, SIRT3 inhibits the NLRP3 inflammasome in a mouse model of sepsis-induced acute kidney injury by attenuating ROS production [92], and is also protective in a model of LPS-induced lethality [93]. SIRT3 deficiency accelerates the development of metabolic syndrome in mouse, and single nucleotide polymorphisms in the human SIRT3 gene have been associated with this condition [40].…”
Section: Sirtuins As Metabolic Sensors That Regulate Inflammationmentioning
confidence: 99%